Using a Church as a Temporary Auditorium. Acoustical Design of S. Domenico of Imola. (October 2020) - Merli, F; Bevilacqua, A
Abstract: In Europe, many of the ancient buildings, especially sacred architecture, are subject to renovation projects by converting their initial occupation type for temporary exposition. In particular, the demand for assisting to live musical performance is increased considerably in Italy because of the missing of places dedicated to the performing arts. As such, one of the churches of Imola (i.e. San Domenico), located approximately 30 Km far from Bologna, has been requested by citizens to be adapted into an auditorium when necessary. Based on needs expressed by the local population, this paper recommends one of the possibilities of how the acoustical design can be applied to the church in order to adjust the main volume to the realization of transient musical venues, cancelling any undesirable reflections that can lower the quality perception of sound. The actual acoustics has been adapted in order to reach both speech and musical intelligibility, especially focused on sacred music style. Both measured and simulated results have been compared determining the choice of the proposed acoustical solutions in terms of type of finishes and surface area to be covered by the added materials. The suitable treatments in consideration include absorbing wooden panels, curtains and fabric wrap.